The Information security tools in an automated system for secure information exchange : Information security tools in an automated system for secure information exchange - Begimbayeva, Yenlik; Ussatova, Olga; Biyashev, Rustem; Smolarz, Andrzej; Abisheva, Akmaral (ADVANCED TECHNOLOGIES AND COMPUTER SCIENCE, 2020)
The article presents information security tools to ensure the secure exchange of information in an automated system. A model of information security for an automated information exchange system is proposed. This model will increase the level of information security in electronic document flow in the cross-border space.